Modeling antibody persistence after MenACYW-TT vaccination and comparative analysis with other quadrivalent meningococcal vaccines - Laurent Coudeville; Isabelle Bertrand-Gerentes; Céline Zocchetti; Edith Langevin; Siham Bchir; Florence Coste; Philipp Oster (Scientific Reports)
Abstract Evaluating the persistence of antibody titers produced by quadrivalent meningococcal vaccines is crucial for determining the optimal timing for primary and booster doses. Using 3 − 7-year persistence data after a single priming dose of MenACYW-TT to fit a statistical model of antibody decay over time (10 years), this analysis modeled long-term antibody persistence for this vaccine in toddlers (12–23 months), adolescents/young adults (13–26 years), and older adults (≥ 56 years), comparing it with other vaccines (MCV4-TT, MenACWY-CRM, MPSV4). The statistical model is based on a Bayesian approach and it accounts for vaccine- and age group-specific antibody decline, missing data, assay errors, and antibody boosting from breakthrough infections. At 10 years post-vaccination, it predicted comparable or higher seroprotective immunopersistence for MenACYW-TT (titers ≥ 1:8 with hSBA) versus (1) MCV4-TT in toddlers (77% [95% CI 70–84] vs. 17% [6–31] for serogroup C, 67% [59–74] vs. 36% [20–53] for serogroup W); (2) MenACWY-CRM in adolescents/young adults (63% [55–71] vs. 40% [32–48] for serogroup C, 67% [59–74] vs. 57% [47–67] for serogroup W); and (3) MPSV4 in older adults (31% [23–39] vs. 22% [14–29] for serogroup C, 38% [31–46] vs. 20% [14–27] for serogroup W). In conclusion, our analysis indicated similar or higher immune persistence at 10 years for MenACYW-TT compared with other quadrivalent meningococcal vaccines, particularly for serogroups C and W.